Optimization of Samarium(III) Sorption using Nano-Zirconium Oxide by Taguchi Method - Dubey, Som Shankar; Grandhi, Sarika (Asian Journal of Chemistry, 2019)
Sorption of samarium on nano zirconium oxide was carried out as a function of pH, contact time, initial metal ion concentration and temperature. Taguchi’s L-25 orthogonal array was adopted to identify the most influential factors accountable for enhanced sorption of Sm(III). In Taguchi analysis the sorption amounts (Qt) of Sm(III) ions were directed into an precise S/N ratio for a “high is better” response. By examining signal-to-noise ratio (S/N) the quality trail can be determined. The experiment performed under optimum conditions as predicted by Taguchi method resulted in enhanced Sm(III) sorption by zirconium oxide with minimum error. Analysis of variance indicated that the pH of Sm(III) is the most influential factor for high amount of sorption (Qt). Maximum sorption of 21.3 mg/g (Qe) was noticed from the solution of initial metal [samarium] ion concentration 0.5 ppm, temperature of 323 K, pH 6.9 and contact time of 50 min [Taguchi optimized factors]. Sorption followed both Dubinin- Radushkevich and Langmuir isotherms. The free energy of sorption was found to be 18.3 kJ mol-1. Pseudo second-order equation well fitted for the sorption kinetics. Sorption increased with increase in temperature. Sorption was endothermic in nature. Reichenburg equation was used to explain the diffusion process. The value of ΔG° was also evaluated. X-ray diffraction and high resolution transmission electron microscopy data supported that the size of the sorbent as 15.5 nm.